Study Literatur Hawalah dan Ji’alah : Implementasi dan Aplikasinya Akad pada Transaksi Bank Syariah - Yori Kurniawati; Kiki Razroma Yantika; Riski Murdani; Aidil Alfin (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to examine the Literature Study of Hawalah and Ji'alah: Implementation and Application of Akad in Sharia Bank Transactions. This method aims to develop the Study of Hawalah Dan Ji'alah Literature: Implementation and Application of Akad in Sharia Bank Transactions, focusing on the application of application in daily life. The data in this study was collected through the search of relevant documents and secondary sources, such as: Articles from national and international journals indexed by SINTA and Scopus, related to the Literature Study of Hawalah Dan Ji'alah and its Application of Akad in Sharia Bank Transactions. The results of the research are that the Hawalah and Ji'alah Contracts are part of the muamalah instrument in Islam which has an important function in regulating sharia economic activities. Hawalah as a debt transfer mechanism has evolved from traditional practices to financial instruments used in various Islamic banking services such as credit cards and factoring. Meanwhile, Ji'alaj as a contract to provide rewards for a service or work whose results are uncertain, provides space for flexibility in various fields such as education, business, and technology.